The Humanitarian Perspectives in The Novels of Ghazi Al- Gosaibi - Al- Ghamdi, Ahmad Ibrahim (Journal of Humanities & Social Sciences, 2022)
The study aims to explore the humanitarian perspectives in the novels of Ghazi bin Abdul Rahman Al- Gosaibi. It analyzes some human aspects such as poverty and its impact on Arab societies, disease and disability and their impact on humans, the dream of every human being to achieve freedom, and the ambition of most people to enjoy peace. The study employs these aspects in the novels of Ghazi Al- Gosaibi. The study reached a number of findings, most notably: Ghazi Al- Qusaybi was occupied with the human dimension in his writings, including his novels. Poverty, disease and disability were enriching material for his novels. Moreover, he has worked to establish the principle of freedom in Arab societies, and sought in his novels to spread peace in Arab countries. His ambition may have been to achieve peace in the world in general, including his condemnation of the two world wars and the human and material losses it has left. He also condemned the Israeli war against the Palestinians. The study recommends the following: Expanding the academic researches which study the Saudi novel, including the novels of Ghazi Al- Gosaibi. Also, increasing the literary, critical and social studies in Ghazi Al- Gosaibi’s works. The researchers should explore Al- Gosaibi’s texts to reach a deep understanding of the Arab situation. They are also recommended to focus on studying the social conditions as portrayed in the Saudi novel, paying special attention to the works of Ghazi Al- Gosaibi due to its philosophical depth.